2015
DOI: 10.14310/horm.2002.1573
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sleep and light at night on melatonin in adolescents

Abstract: OBJECTIVE: The circadian hormone melatonin has wide-reaching effects on human physiology. In adolescents, the impact of nighttime light exposure and other modifiable behavioral factors on melatonin levels is poorly understood. DESIGN: We cross-sectionally examined the influence of nighttime behaviors on melatonin levels in 100 adolescents (average age: 15.7; 55 female, 45 male), who completed a self-administered questionnaire and provided a first morning urine sample to assay for urinary 6-sulfatoxymelatonin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The results of the present study shows that there is no significant difference in melatonin secretion in the students with late bedtime. Similar type of result was that, the night-time behaviours of adolescents, did not impact urinary melatonin levels [33].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The results of the present study shows that there is no significant difference in melatonin secretion in the students with late bedtime. Similar type of result was that, the night-time behaviours of adolescents, did not impact urinary melatonin levels [33].…”
Section: Discussionsupporting
confidence: 65%
“…Also increased prevalence of anxiety and depression is seen in females as compared to males. Literature studies have shown increased melatonin levels in females than in males [23,24,25]. Though other studies of melatonin in adolescents did not find significant sex differences [26,27] .…”
Section: Introductionmentioning
confidence: 86%
“…All participants were required to follow a consistent sleep-wake schedule (bedtimes no later than 23:00 and wake times no later than 08:00) during the week before the study day to the end of the study, to maintain their daytime serum melatonin circadian rhythm. [42][43][44] The sleep-wake schedule execution and physical condition of each participant were tracked every day. Light treatment was performed in a closed space and regular examinations were conducted during the study to ensure that none of the participants had closed their eyes (except for blinking), so that their status could meet the requirements of the study.…”
Section: Protocolmentioning
confidence: 99%
“…Dear Editor, It was with great interest that we read the recent study by Hersh et al 1 on the effects of sleep and light at night on melatonin in adolescents. Of particular interest was their focus on electronic use after "lights out".…”
Section: Letter To the Editormentioning
confidence: 99%